3-D multiphysics simulation on electrolyte membrane dehumidification considering the real air channel and collection layer structures. (September 2021) - Li, Heyong; Qi, Ronghui; Zhang, Li-zhi
Highlights: 3-D multiphysics model was developed for PEM-based dehumidificer considering real structures of multilayers. The parameters changed rapidly in first 200s during start-up, and attaining stable at 1200 s. As air flowrate and voltage doubled, the start-up time of system was reduced by 50% and 67%. Highest temperature and lowest humidity of airflow occurred at the anode-side corner away from the inlet. The structure of anode collector showed significant effect on field distributions of PEM dehumidifier. Abstract: Predicting the dynamic multiphysics distribution of electrolyte membrane-based dehumidification is critical but still challenging. This study established a 3-D multi-physics model of electrolytic dehumidification, considering the real structures of dehumidification components. The dynamic field distributions under different start-up conditions were numerically simulated. This model was validated by experiments, showing an error within the range of 10%. Results showed that in the first 200s, all the parameters changed rapidly, especially in the stoma edge of the CLA, before finally attaining a stable state at approximately 1200 s. The start-up time mainly changed with air mass flow rate and voltage. When air mass flow rate and voltage were doubled, the start-up time of system was reduced by 50% and 67%, respectively. Furthermore, during start-up, the highest temperature (357.5K) occurred at the edge of PEM, and the temperature difference between the position corresponding to the orifices in the titanium-mesh collector and the highest temperature was up to 40K. Besides, for the CLA, the water vapor concentration at the position corresponding to the orifices in the titanium-mesh collector is higher, and the highest current density occurred at the stoma edge of the collector layer. For the air channel, the highest temperature and lowest water vapor concentration occurred at the anode-side corner away from the air inlet. Compared to that of air channel, the structure of collector layer, especially the anode-side one, showed more obvious effect on the field distributions inside the multilayers, and the dehumidification performance accordingly. This research revealed the 3-D dynamic characteristics inside the dehumidification elements considering real structures of air channel and collection layer, which is of great significance for optimizing the system operating performance. Graphical abstract: Image, graphical abstract